Here Come the Bridesmaids! - Martin, Ann M., 1955- (New York Scholastic Inc., 1994)
When two weddings give three club members the opportunity to be bridesmaids, Claudia and Dawn excitedly fly out to California to participate in Dawn's father's nuptials, while an enthusiastic Stacey attends Mrs. Barrett in Stoneybrook
Include Illustration
Keywords: Babysitters -- Weddings -- Babysitters Club (Imaginary organization)